Cyclic tests on steel truss-embedded steel plate-concrete composite walls. (December 2022) - Xu, Kai-Yuan; Xu, Dan; Yan, Jia-Bao; Wang, Tao
Abstract: This paper performed five cyclic tests to investigate seismic performances of novel steel truss-embedded steel plate-concrete composite wall (STSCW) specimens with different prepared parameters. The studied key parameters included the cross-section size of chord member, truss-to-wall ratio, and steel–concrete interface without studs. The STSCWs experienced progressive failures of steel faceplate buckling, vertical weld fracture in the bottom corner, concrete crushing, and steel faceplate tensile fracture. Moreover, the failure modes of embedded steel truss consisted of flange necking or fracture under tension and local buckling under compression. The effects of these key parameters on seismic behaviors of STSCWs were analyzed and discussed. They showed that increasing the truss-to-wall ratio and cross-section size of the chord member improved the lateral shear resistance and deformation capacity of STSCWs. Welding studs to the flange had a negligible effect on the lateral shear resistance but reduced the deformation capacity of STSCWs. Moreover, welding studs to the flange improved the deformation compatibility between the wall and steel truss. A theoretical model was developed and validated, indicating that the predicted lateral resistances agreed well with test results.